1984
DOI: 10.1007/bf00026607
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of the zooplankton community in the Cabo Frio region (Brazil) influenced by coastal upwelling

Abstract: Cabo Frio area (Central-southern Brazilian littoral) is characterized by a coastal upwelling due to prevailing E-NE winds, mainly during the spring-summer season .The geographic distribution of the zooplankton was described in order to separate ecological areas in terms of specific communities . Cluster analysis by weighted pair-group method (W PGA) and principal component (PC) analysis was performed on the most important hydrological parameters and zooplankton taxa . The first PC, explaining 38% of the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 8 publications
1
4
1
1
Order By: Relevance
“…Oithona attenuata is recorded here for the first time off Brazil, even though several studies had previously been conducted in the same place (Valentin, 1984;Dias and Araujo, 2006;Dias et al, 2010;Rosa and Monteiro-Ribas, 2012;Rosa et al, 2016). Its absence in plankton samples over the last 30 years leads us to suggest that this species was brought to Brazilian waters as an exotic species.…”
Section: Oithona Attenuata From Brazilsupporting
confidence: 46%
“…Oithona attenuata is recorded here for the first time off Brazil, even though several studies had previously been conducted in the same place (Valentin, 1984;Dias and Araujo, 2006;Dias et al, 2010;Rosa and Monteiro-Ribas, 2012;Rosa et al, 2016). Its absence in plankton samples over the last 30 years leads us to suggest that this species was brought to Brazilian waters as an exotic species.…”
Section: Oithona Attenuata From Brazilsupporting
confidence: 46%
“…100 m −3 ) and larvae (>100 ind. 100 m −3 ), once the enhancement of the primary and secondary production ensure the availability of food for the future larvae [27], [33]. This is especially required during the critical period [75].…”
Section: Discussionmentioning
confidence: 99%
“…Coastal upwelling due to wind and topographic effects, occurs in the northern portion of the study area (CSTF) [32], [33], especially during austral spring and summer, due to prevalent northeasterly winds. The cold and nutrient-rich SACW is upwelled and provides special conditions for high primary production levels along the coastline.…”
Section: Methodsmentioning
confidence: 99%
“…The Arabian Sea and coasts of Namibia, Chile, Peru and Benguela display areas where upwelling phenomena occur in a more pronounced way [1][4]. Some studies have confirmed the existence of a typical upwelling system on the southeast Brazilian coast and that the Arraial do Cabo region is the location where the main event occurs [5][7]. In this region, the South Atlantic Central Water (SACW) rises to the surface of the ocean in accordance with the east-northeast winds that occur more frequently between spring and summer and also due to the influence of cyclonic meanders [8][11].…”
Section: Introductionmentioning
confidence: 98%